(untitled) (International Journal of Engineering and Computer Science, 2018)
One of the major reasons for road accidents now a days is due to driver fatigue. Be it long distant travelling or drunk driving drowsy state leads to risky crashes which is hazardous to lives as well. To overcome such accidents some method has to be developed that is feasible to all vehicle drivers . This paper is a survey based on various methods for preventing road accidents and designs on drowsiness detection methods which were proposed and have advantages and disadvantages